Prior Hypoxia Exposure Enhances Murine Microglial Inflammatory Gene Expression in vitro Without Concomitant H3K4me3 Enrichment - Kiernan, Elizabeth A.; Ewald, Andrea C.; Ouellette, Jonathan N.; Wang, Tao; Agbeh, Abiye; Knutson, Andrew O.; Roopra, Avtar S.; Watters, Jyoti J. (Frontiers in Cellular Neuroscience, 2020)
1 Hypoxia is a component of multiple disorders, including stroke and sleep-disordered breathing, that often precede or are comorbid with neurodegenerative diseases. However, little is known about how hypoxia affects the ability of microglia, resident CNS macrophages, to respond to subsequent inflammatory challenges that are often present during neurodegenerative processes. We therefore tested the hypothesis that hypoxia would enhance or “prime” microglial pro-inflammatory gene expression in response to a later inflammatory challenge without programmatically increasing basal levels of pro-inflammatory cytokine expression. To test this, we pre-exposed immortalized N9 and primary microglia to hypoxia (1% O2) for 16 hrs and then challenged them with pro-inflammatory lipopolysaccharide (LPS) either immediately or 3-6 days following hypoxic exposure. We used RNA sequencing coupled with chromatin immunoprecipitation sequencing to analyze primed microglial inflammatory gene expression and modifications to histone H3 lysine 4 trimethylation (H3K4me3) at the promoters of primed genes. We found that microglia exhibited enhanced responses to LPS 3 days and 6 days post-hypoxia. Surprisingly however, the majority of primed genes were not enriched for H3K4me3 acutely following hypoxia exposure. Using the bioinformatics tool MAGICTRICKS and reversible pharmacological inhibition, we found that primed genes required the transcriptional activities of NF-ĸB. These findings provide evidence that hypoxia pre-exposure could lead to persistent and aberrant inflammatory responses in the context of CNS disorders.